A Series of Thiadiazolyl‐Benzenesulfonamides Incorporating an Aromatic Tail as Isoform‐Selective, Potent Carbonic Anhydrase II/XII Inhibitors. (9th March 2022) - Banoglu, Erden; Ercanlı, Taner; Gür Maz, Tuğçe; Vullo, Daniela; Bonardi, Alessandro; Gratteri, Paola; Supuran, Claudiu T.
Abstract: We describe the synthesis of a series of thiadiazolyl‐benzenesulfonamide derivatives carrying an aromatic tail linked by an amide linker (12–34 ), as human carbonic anhydrase (hCA) inhibitors. These thiadiazol derivatives were evaluated against four physiologically relevant CA isoforms (hCA I, II, IX, and XII), and demonstrated intriguing inhibitory activity against CA II with Ki values in the range of 2.4–31.6 nM. Besides hCA II, also hCA XII activity was potently inhibited by some of the derivatives (Ki =1.5–88.5 nM), producing dual inhibitors of both isoforms. Notably, compound 17 was the most potent dual CA II (Ki =3.1 nM) and XII (Ki =1.5 nM) inhibitor with a significant selectivity ratio over CA I and IX isoforms. In conclusion, although all compounds exhibited preferential activity towards hCA II, the nature of the substituents at the tail part of the main scaffold influenced the activity and selectivity toward other isoforms. Abstract : A novel scaffold with different tails : hCA II and hCA XII isoforms are involved in the production aqueous humor, and represent attractive therapeutic targets for antiglaucoma drugs. By using a tail approach on a newly designed thiadiazol‐benzenesulfonamide scaffold, we hereby identified novel hCA II and XII inhibitors that warrant further chemical development as novel candidates for antiglaucoma drug development.